Pengaruh Kualitas Produk, Lokasi Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Produk Roti “Java Bakery” Di Kecamatan Kandangan Kabupaten Kediri - Rizky Wahyu Septiawan; Bayu Pramutoko; Angga Permana Mahaputra (Transformasi: Journal of Economics and Business Management, 2023)
Improving product quality is the first effort faced by companies, when faced with efforts to become a leader. Products will be judged by quality and that is what adds value to consumers as well as one of the reasons for choosing to buy. Other factors that influence the decision to purchase Java Bakery bread products are location and quality of service. Therefore, businesses that want to stay ahead of their competitors need to take a number of actions related to improving product quality, improving location and service quality. This research is a descriptive quantitative research that aims to produce a discovery obtained through statistical procedures. The sample in this study used accidental sampling with a total of 97 respondents. The data in this study were obtained through interviews and questionnaires. From the results of the analysis that has been done. The results of the study show that product quality, location and service quality influence purchasing decisions. This is evidenced by the results of the R Square value of 0.563 or 56.3% while the remaining 29.5% is influenced by other variables.